Attitudes, practices, and barriers in tobacco cessation counselling among dentists of Ahmedabad city, India - Sujal Parkar; Ekta Pandya; Abhishek Sharma (Wolters Kluwer Medknow Publications, 2016)
Aim: The aim of this study is to investigate the attitudes and practices of dentists from Ahmedabad with respect to their roles in tobacco cessation counselling and to find the barriers to such activity that prevents them to do so. Materials and Methods: A total of 150 dentists of Ahmedabad city were contacted at their dental office. The questionnaire was given to them and the responses were recorded. The questionnaire comprised of demographic details and 13-item questionnaire related to attitudes, practices, and barriers among dentists for tobacco cessation counselling. The frequencies of the responses were calculated, and the variables were compared using Chi-square test. Results: A total of 121 questionnaires were returned with the response rate of 80.66%. Out of 121 respondents, 60 (49.6%) were male dentists and 61 (50.4%) were female dentists. Age of dentists varied from 23 to 46 years, with mean age of 31.21 ± 7.31 years. Most of the dentists strongly believed that it is their responsibility to educate the patients regarding tobacco cessation counselling. More than half of the participant dentists do satisfactory tobacco cessation counselling during their dental practice. They feel restrained when it comes to prescribing nicotine replacement therapy. The lack of proper training was found to be the major barrier for tobacco cessation counselling. Conclusion: Dentist has a positive attitude for tobacco cessation counselling, but lack of proper training is a significant barrier for their failure. Hence, dentists should be given proper training for tobacco cessation counselling during their studies or continuing dental education programs should be arranged.